2012
DOI: 10.1371/journal.pone.0036453
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Sim1 Neurons Causes Obesity through Hyperphagia and Reduced Energy Expenditure

Abstract: Single-minded 1 (Sim1) is a transcription factor necessary for development of the paraventricular nucleus of the hypothalamus (PVH). This nucleus is a critical regulator of appetite, energy expenditure and body weight. Previously we showed that Sim1+/− mice and conditional postnatal Sim1−/− mice exhibit hyperphagia, obesity, increased linear growth and susceptibility to diet-induced obesity, but no decrease in energy expenditure. Bilateral ablation of the PVH causes obesity due to hyperphagia and reduced energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 60 publications
(90 reference statements)
5
68
1
Order By: Relevance
“…46,47 Sim1 neuron ablation in adult mice induces hyperphagic obesity. 48 In humans, SIM1 disruption due to an apparently balanced translocation caused severe obesity and hyperphagia in a girl. 49 Obesity was a feature in several patients with 6q16 deletion and SIM1 deficiency (Figure 3 and Table 3).…”
Section: Cytogenetic and Molecular Resultsmentioning
confidence: 99%
“…46,47 Sim1 neuron ablation in adult mice induces hyperphagic obesity. 48 In humans, SIM1 disruption due to an apparently balanced translocation caused severe obesity and hyperphagia in a girl. 49 Obesity was a feature in several patients with 6q16 deletion and SIM1 deficiency (Figure 3 and Table 3).…”
Section: Cytogenetic and Molecular Resultsmentioning
confidence: 99%
“…This SNP was also nominally associated with total ASD scores and social interaction impairment. SIM1 has been previously studied for associations with obesity and hyperphagia, with a demonstrated lowering of hypothalamic oxytocin mRNA expression (Xi et al, 2012) and oxytocin peptide levels (Kublaoui et al, 2008) in SIM1 haploinsufficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…It has so far been studied mainly with a focus on hyperphagia and obesity, with an effect demonstrated by mice haploinsufficient for the SIM1 gene (Xi et al, 2012). It has been shown that SIM1 is important for oxytocin expression in the PVN, with a near 80% reduction in haploinsufficient mice (Kublaoui et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This implies that Mc4r and Sim1 are coexpressed in a subset of neurons and that Mc4r in these neurons is critical to the central melanocortin pathway, which influences body weight by modulating food intake independently of energy expenditure (37). However, targeted ablation of Sim1-expressing neurons with diphtheria toxin resulted in obesity resultant from both hyperphagia and reduced energy expenditure, suggesting additional Sim1 independent roles exist in at least some Sim1-expressing neurons to regulate energy balance (38).…”
Section: Figurementioning
confidence: 99%